2022
DOI: 10.1097/md.0000000000030997
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic findings of gastric neoplasms in familial adenomatous polyposis are associated with the phenotypic variations and grades of dysplasia

Abstract: Patients with familial adenomatous polyposis (FAP) are at increased risk of developing gastric neoplasms. However, endoscopic findings have not been sufficiently investigated. We investigated the phenotypic expression of gastric adenoma (low-grade dysplasia) and gastric cancer (high-grade dysplasia or carcinoma) in patients with FAP and clarified their relationships to endoscopic findings. Of 29 patients with FAP who underwent esophagogastroduodenoscopy between 2005 and 2020, 11 (38%) had histologically confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…While the incidence of gastric cancer among these patients ranged from 0.6% to 1.3% in Western cohorts with no significant difference from that in the general population, the rate of gastric cancer co-occurrence in Japan was notably higher, ranging from 3.1% to 4.2% [6]. In a previous study, we examined 29 patients with familial adenomatous polyposis who underwent an esophagogastroduodenoscopy [14]. Our analysis found that eleven patients (38%) had confirmed gastric neoplasms, including twenty-three gastric adenomas and nine gastric cancers.…”
Section: Introductionmentioning
confidence: 99%
“…While the incidence of gastric cancer among these patients ranged from 0.6% to 1.3% in Western cohorts with no significant difference from that in the general population, the rate of gastric cancer co-occurrence in Japan was notably higher, ranging from 3.1% to 4.2% [6]. In a previous study, we examined 29 patients with familial adenomatous polyposis who underwent an esophagogastroduodenoscopy [14]. Our analysis found that eleven patients (38%) had confirmed gastric neoplasms, including twenty-three gastric adenomas and nine gastric cancers.…”
Section: Introductionmentioning
confidence: 99%